2017
DOI: 10.1016/j.nanoen.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

High-performance piezo-phototronic solar cell based on two-dimensional materials

Abstract: Pieoztronic and piezo-phototronic are two emerging fields of flexible electronics and nanoelectronics using by piezoelectric semiconductor materials, such as ZnO, GaN, InN and CdS. Recent experiments shown piezoelectric and semiconductor properties of monolayer MoS 2, which have been applied as nanogenertor and piezotronic transistor. Two-dimensional piezoelectric semiconductor can be utilized for high-performance photovoltaic devices. In this paper, a two-dimensional material piezo-phototronic solar cell is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 30 publications
0
45
1
Order By: Relevance
“…Recently, 2D MoS 2 with single‐atomic‐layer has also manifested a piezoelectric property, which reveals potential applications of 2D materials in powering nanodevices, wearable devices, and tactile sensors. Thanks to the excellent photoelectric, piezoelectric, and mechanical performances, it can be used for energy conversion and piezotronics, and even for high‐performance piezo‐phototronic solar cells …”
Section: Theory Of Piezo‐phototronicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, 2D MoS 2 with single‐atomic‐layer has also manifested a piezoelectric property, which reveals potential applications of 2D materials in powering nanodevices, wearable devices, and tactile sensors. Thanks to the excellent photoelectric, piezoelectric, and mechanical performances, it can be used for energy conversion and piezotronics, and even for high‐performance piezo‐phototronic solar cells …”
Section: Theory Of Piezo‐phototronicsmentioning
confidence: 99%
“…All the above discussions are assumed that the J sc has no connection with the external strain . Weakening light reflection and enhancing light absorption are needed to promote J sc .…”
Section: Theory Of Piezo‐phototronicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mechanism also holds for a case of an n‐type non‐piezoelectric material and a p‐type piezoelectric material as shown in Figure (c) and (d). More details about theoretical studies of piezo‐phototronic effect on a solar cell can be found in numerous references …”
Section: Piezotronic and Piezo‐phototronic Effect On A Quantum Dot Somentioning
confidence: 99%